2018
DOI: 10.12928/telkomnika.v16i2.5895
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Enterprise Resource Planning (ERP) Systems Effectiveness in Indonesia

Abstract: Refining DeLone and McLean's (D&M) information system model and technology-organisationenvironment (TOE) framework, this research identifies the prominent factors that determine ERP system success. Hypotheses are also drawn based on supporting theories to evaluate the causal relationship between the success determinants. The level of achievement is measured by system quality, information quality, service quality, external quality and top management support, which intermediated by perceived usefulness and user … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(3 reference statements)
1
5
0
Order By: Relevance
“…According to the fndings, system quality is signifcantly associated with perceived ease of use, but not with perceived usefulness. Prior studies have verifed that system quality has a signifcant impact on perceived ease of use [11,60] and perceived usefulness [10,12]. Tese results could be elaborated by the fact that the better performance of the SNS system increases the level of perceived ease of use, but not perceived usefulness.…”
Section: Mobile Information Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the fndings, system quality is signifcantly associated with perceived ease of use, but not with perceived usefulness. Prior studies have verifed that system quality has a signifcant impact on perceived ease of use [11,60] and perceived usefulness [10,12]. Tese results could be elaborated by the fact that the better performance of the SNS system increases the level of perceived ease of use, but not perceived usefulness.…”
Section: Mobile Information Systemsmentioning
confidence: 99%
“…System quality represents the expected characteristics of an SNS, including adaptability, reliability, availability, and usability [58,59]. Several studies triggered the conclusion that system quality has a signifcant efect on perceived ease of use [11,60,61]. Prior research revealed that system quality is signifcantly associated with perceived usefulness [10,12,62].…”
Section: Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its wide range of practical applications, ERP system is an equally active area of research interest [13]. Researches about ERP concern: the general frame of literature, the software and its optimization, the identification of factors that contribute to the adoption and the selection of those systems, the advantages and disadvantages of ERP implementation and finally, the efficiency estimation of ERP implementation [11,[13][14][15][16][17][18][19]. The identification of factors that are adjudged critical in ERP implementation success [9, 20 etc.…”
Section: Introductionmentioning
confidence: 99%